Numerical Investigation of SPP Propagation at the Nano-scale MDM Waveguides with a Combiner - Saber, Md. Ghulam; Sagor, Rakibul Hasan; Noor, Asif Al; Al-Amin, Md. Thesun (Photonics Letters of Poland, 2013)
We present the propagation characteristics of Surface Plasmon Polariton in the nanoscale Metal-Dielectric-Metal waveguides which consist of a combiner. The propagation loss due to absorption by metal and reflection at the point of recombination are analyzed numerically. We have investigated the structure with different dielectric materials (air, aluminum gallium arsenide, gallium lanthanum sulfide) and for different wavelengths of the input signal. The wavelength dependent reflection coefficient, return loss and voltage standing wave ratio have also been reported in order to analyze the performance of the combiner. Full Text: PDF References T. W. Ebbesen, H. Lezec, H. Ghaemi, T. Thio, and P. Wolff, "Extraordinary optical transmission through sub-wavelength hole arrays", Nature 391 (1998) 667. CrossRef D. K. Gramotnev and S. I. Bozhevolnyi, "Plasmonics beyond the diffraction limit", Nature Photonics 4 (2010) 83. CrossRef A. J. Haes and R. P. Van Duyne, "A Nanoscale Optical Biosensor: Sensitivity and Selectivity of an Approach Based on the Localized Surface Plasmon Resonance Spectroscopy of Triangular Silver Nanoparticles", Journal of the American Chemical Society 124 (2002) 10596. CrossRef J. Henzie, M. H. Lee, and T. W. Odom, "Multiscale patterning of plasmonic metamaterials", Nature nanotechnology 2 (2007) 549. CrossRef A. Hosseini and Y. Massoud, "A low-loss metal-insulator-metal plasmonic bragg reflector", Optics express 14 (2006) 11318. CrossRef V. E. Ferry, L. A. Sweatlock, D. Pacifici, and H. A. Atwater, "Plasmonic Nanostructure Design for Efficient Light Coupling into Solar Cells", Nano Lett. 8 (2008) 4391. CrossRef H. Ditlbacher, A. Hohenau, D. Wagner, U. Kreibig, M. Rogers, F. Hofer, F. R. Aussenegg, and J. R. Krenn, "Silver Nanowires as Surface Plasmon Resonators", Phys. Rev. Lett. 95 (2005) 257403. CrossRef W. Saj, T. Antosiewicz, J. Pniewski, and T. Szoplik, "Energy transport in plasmon waveguides on chains of metal nanoplates", Opto-Electronics Review 14 (2006) 243. CrossRef G. S. Blaustein, M. I. Gozman, O. Samoylova, I. Y. Polishchuk, and A. L. Burin, "Guiding optical modes in chains of dielectric particles", Opt. Express 15 (2007) 17380. CrossRef H. Shin and S. Fan, "All-Angle Negative Refraction for Surface Plasmon Waves Using a Metal-Dielectric-Metal Structure", Phys. Rev. Lett. 96 (2006) 73907. CrossRef G. Veronis and S. Fan, "Bends and splitters in metal-dielectric-metal subwavelength plasmonic waveguides", Applied physics letters 87 (2005) 131102. CrossRef H. Gao, H. Shi, C. Wang, C. Du, X. Luo, Q. Deng, Y. Lv, X. Lin, and H. Yao, "Surface plasmon polariton propagation and combination in Y-shaped metallic channels", Optics express 13 (2005) 10795. CrossRef B. Wang and G. P. Wang, "Surface plasmon polariton propagation in nanoscale metal gap waveguides", Opt. Letters 29 (2004) 1992. CrossRef K. Yee, "Numerical solution of initial boundary value problems involving maxwell's equations in isotropic media", IEEE Transactions on Antennas and Propagation, 14 (1966) 302. CrossRef M. A. Alsunaidi and A. A. Al-Jabr, "A General ADE-FDTD Algorithm for the Simulation of Dispersive Structures", IEEE Photonics Technology Letters, 21 (2009) 817. CrossRef A. D. Rakic, A. B. Djurišic, J. M. Elazar, and M. L. Majewski, "Optical Properties of Metallic Films for Vertical-Cavity Optoelectronic Devices", Applied optics 37 (1998) 5271. CrossRef M. Alsunaidi and F. Al-Hajiri, Proc. PIERS, p.1694 (2009). DirectLink R. H. Sagor, "Plasmon Enhanced Symmetric Mode Generation in Metal-Insulator-Metal Structure with Kerr Nonlinear Effect", International Journal of Computer Applications 50 (2012) 24. CrossRef